2008
DOI: 10.1128/jb.00134-08
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Characterization of the Poly(3-Hydroxybutyrate- co -3-Hydroxyvalerate) Synthase in Haloferax mediterranei

Abstract: The haloarchaeon Haloferax mediterranei has shown promise for the economical production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), a desirable bioplastic. However, little is known at present about the genes involved in PHBV synthesis in the domain Archaea. In this study, we cloned the gene cluster (phaEC Hme ) encoding a polyhydroxyalkanoate (PHA) synthase in H. mediterranei CGMCC 1.2087 via thermal asymmetric interlaced PCR. Western blotting revealed that the phaE Hme and phaC Hme genes were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
152
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(158 citation statements)
references
References 42 publications
4
152
0
2
Order By: Relevance
“…mediteranneimediated PHA production has been further optimized by researchers all around the world. Whereas some of these groups focused on the application of inexpensive carbon feedstocks to safe substrate costs, such as whey permeate from dairy industry [12,13,48], rice-based ethanol stillage [49], extruded rice bran [50], enzymatically extruded starch [51], crude glycerol phase [28], olive mill waste water [52], vinasse [53], etc., others clarified the enzymatic and genetic background of PHA-synthesis [54][55][56][57] and in vitro degradation [58] by this organisms. Mathematic models of PHA-production [59], and kinetic studies of PHA and by-product synthesis and degradation [60] were reported for Hfx.…”
Section: Discussionmentioning
confidence: 99%
“…mediteranneimediated PHA production has been further optimized by researchers all around the world. Whereas some of these groups focused on the application of inexpensive carbon feedstocks to safe substrate costs, such as whey permeate from dairy industry [12,13,48], rice-based ethanol stillage [49], extruded rice bran [50], enzymatically extruded starch [51], crude glycerol phase [28], olive mill waste water [52], vinasse [53], etc., others clarified the enzymatic and genetic background of PHA-synthesis [54][55][56][57] and in vitro degradation [58] by this organisms. Mathematic models of PHA-production [59], and kinetic studies of PHA and by-product synthesis and degradation [60] were reported for Hfx.…”
Section: Discussionmentioning
confidence: 99%
“…H. mediterranei grows faster than most other members of Halobacteriaceae and exhibits remarkable metabolic efficiency and genome stability at high salt concentrations (15,19) and thus has served as a good model for haloarchaeal physiology and metabolism studies for several decades (1, 3, 5, 11, 13). In particular, H. mediterranei is capable of accumulating poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) from many cheap carbon sources (12,17,18). Two key enzymes (PhaEC and PhaB) and a structure protein (PhaP) involved in PHBV biosynthesis have been identified in H. mediterranei (2,6,9,17).…”
mentioning
confidence: 99%
“…However, the PhaC subunits of halophilic archaea are much larger and contain a longer C terminus than their bacterial counterparts, and the haloarchaeal PhaE subunits (~20 kD) are much smaller than those of bacteria (~40 kD). Western blotting analysis revealed that both PhaC and PhaE are bound to the PHA granules in H. mediterranei, whereas in H. marismortui, only PhaC has been demonstrated to be strongly bound to the PHA granules [15,16]. While the PHA synthases of haloarchaea have shown some homology to the bacterial synthases, the other PGAPs, i.e., the depolymerase PhaZ, regulator PhaR and the phasin PhaP, found in bacteria, have not been identified in any haloarchaeal genome, indicating that they may be quite distinct from their bacterial counterparts.…”
Section: Polyhydroxyalkanoate (Pha) Granule Associated Proteinsmentioning
confidence: 99%